Tumor markers in pancreatic cancer: a European Group on Tumor Markers (EGTM) status report - Duffy, M J; Sturgeon, C; Lamerz, R; Haglund, C; Holubec, V L; Klapdor, R; Nicolini, A; Topolcan, O; Heinemann, V (Annals of oncology, 2010)
Pancreatic ductal adenocarcinoma is one of the most difficult malignancies to diagnose and treat. The aim of this article is to review how tumor markers can aid the diagnosis and management of patients with this malignancy. The most widely used and best validated marker for pancreatic cancer is CA 19-9. Inadequate sensitivity and specificity limit the use of CA 19-9 in the early diagnosis of pancreatic cancer. In non-jaundiced patients, however, CA 19-9 may complement other diagnostic procedures. In patients with resectable pancreatic cancer, presurgical and postresection CA 19-9 levels correlate with overall survival. In advanced disease, elevated pretreatment levels of CA 19-9 are associated with adverse patient outcome and thus may be combined with other factors for risk stratification. Most, but not all, reports indicate that serial levels of CA 19-9 correlate with response to systemic therapy. Use of CA 19-9 kinetics in conjunction with imaging is therefore recommended in monitoring therapy. Although several potential serum and tissue markers for pancreatic cancer are currently undergoing evaluation, none are sufficiently validated for routine clinical use. CA 19-9 thus remains the serum pancreatic cancer marker against which new markers for this malignancy should be judged.
Keywords: Biomarkers, Tumor; nádorové biomarkery; nádory slinivky břišní; Humans; lidé; Pancreatic Neoplasms